Sleep assessment and risk of apnea in people with Systemic Arterial Hypertension who use basic health units (UBS) (Research, Society and Development, 2023)
Objective: to assess sleep, risk of apnea and level of sleepiness in people with Systemic Arterial Hypertension (SAH) who use UBS. Methods: clinical, observational and cross-sectional research carried out with 42 people with SAH. Data collection: Participant Profile Questionnaire, Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale and Berlin Clinical Questionnaire. Results and Discussion: of the 42 participants, 24 had poor sleep (57%) or disorder (17%), 67% were at high risk for apnea, and about 31% had excessive sleepiness. When comparing Sleep Quality and Sleepiness between genders, a significant difference was evidenced for the PSQI, with worse sleep for women (p